The Effect of Spokes - Character Credibility on Consumers’ Attitude and Buying Intention : A South African Focus - Mashwama, Vuyelwa; Chiliya, Norman; Chikandiwa, Christopher Tarisayi (Indian Journal of Marketing, 2017)
The recent technological development in animation has provided an attractive alternative to break into the cluttered marketing environment. Created animated spokes-characters can be used as brand endorsers in today’s era. The purpose of this article was to investigate the impact of advertisements and brands that use spokes-characters on purchase intention. The study surveyed 260 respondents in Johannesburg City, South Africa. The study found that consumers like spokes-characters and adverts that use spokes-characters. Moreover, the research findings revealed that only spokes-character attractiveness and expertise influence attitude toward the adverts and spokes-character trust influences attitude towards the brand. In addition, the results reflect that companies can use spokes-characters to improve chances to engage customers about the brand and create long-term relationship and commitment.